Some Problems and Benefits of Advanced Manufacturing Technologies Adoption - Lena Ellitan; Licen Indahwati Darsono (Sinergi: Kajian Bisnis dan Manajemen, 2006)
During the past twenty years, we have witnessed a wide array of advanced manu-facturing technology and computer based technology implemented in varying degree of suc-cess. AMT systems, when properly understood and implemented, can help firms compete along dimensions of cost, quality, flexibility, delivery speed, productivity and even profitability of the firms. Although adoption of Advanced Manufacturing Technology (AMT) promises benefits but are potentially risky. Many firms that have adopted these new technologies have not been able to reap all the potential benefits. In response to the mix result from adoption and imple-mentation of AMTs, this paper attempts to discuss about the issues on factor inducing technol-ogy adoption, some empirical finding on AMT and the role of AMT in manufacturing sectors. There is also growing consensus that many of the failures in adopting AMT are, in fact, due to inadequate planning for, and/or faulty implementation of the systems. The key to successful AMT planning and implementation appears to be choice of an appropriate manufacturing sys-tems and the attainment of an organizational infrastructure that will offer maximum support to the chosen system. The achievement of desired benefit from AMT requires systematic and inte-grated operational planning prior to the adoption of new systems. Such planning requires the identification of likely product and the matching of these products with efficient AMT proc-esses.Keywords: technology, adoption, performance, strategy, implementation